Využití procesů Technology Intelligence v rámci řízení výzkumu a výroby nových léků - Kostrouchová, Veronika; Černý, Jan; Potančok, Martin; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2023)
THE USE OF TECHNOLOGY INTELLIGENCE PROCESSES IN THE MANAGEMENT OF RESEARCH AND PRODUCTION OF NEW DRUGS This thesis focuses on using technology intelligence processes, particularly analyzing patent documents and non-patent literature, to study three model groups of pharmaceutical drugs: medications for thyroid gland disorders, non-steroidal anti-inflammatory drugs and analgesics, and anticancer drugs. By comparing these groups, the thesis aims to identify new research and drug production strategies. The thesis is divided into four parts, which cover the technology intelligence life cycle, specific inputs for technology intelligence, a practical demonstration of the technology intelligence process, and a synthesis of the results with a final discussion.
Vedoucí práce: Jan Černý
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: business analýza [obor dipl. práce]; diplomové práce; master's theses